ESG Disclosure and Financial Performance: The Moderating Role of Firm Size in Indonesian Banking Sector - Fathihani Fathihani; Natalia Santoso; Rini Sulistiyowati; Meilin Veronica (Shirkah: Journal of Economics and Business, 2025)
The evolving global business landscape necessitates that corporations move beyond a singular focus on profitability to integrate sustainability performance through Environmental, Social, and Governance (ESG) principles. This study aims to analyze the effect of ESG disclosure on corporate financial performance, measured by Return on Assets (ROA). It further investigates the moderating role of firm size in the relationship between ESG disclosure and ROA. The research sample comprises banking companies listed on the Indonesia Stock Exchange during the 2020-2024 period. Employing a purposive sampling technique, 10 banks were selected as the final sample based on the consistent publication of their annual and sustainability reports. The data were analyzed using panel data regression and Moderated Regression Analysis (MRA), facilitated by Eviews 12 software. The findings indicate that both environmental and social disclosures exert a significant positive influence on ROA. In contrast, governance disclosure and firm size, as standalone variables, do not demonstrate a significant impact on ROA. Crucially, the analysis confirms that firm size positively moderates the relationship between both environmental and social disclosures and ROA. However, it does not moderate the effect of governance disclosure on financial performance. These results offer significant implications for corporate strategy, underscoring the importance of robust ESG management and the strategic leveraging of firm size to enhance financial outcomes.